Effect of silicon dioxide in sulfur/carbon black composite as a cathode material for lithium sulfur batteries. (March 2019) - Rajkumar, P.; Diwakar, K.; Radhika, G.; Krishnaveni, K.; Subadevi, R.; Sivakumar, M.
Abstract: Lithium-sulfur battery has been recognized as the most promising alternative for energy storage, because of its high theoretical specific capacity and natural abundance. However, owing to the shuttle effect of polysulfides, which leads to the poor cycle life and limits the practical use of LiS batteries. Despite many endeavours in joining sulfur with porous carbon matrix to suppress the polysulfide dissolution, relatively little considerations have been done on silica, but it has a significant role in polysulfide adsorption. Herein, an effective strategy is applied to limit the polysulfide dissolution by using different ratios of sulfur/silicon dioxide/carbon black (S/SiO2 /CB) composite as the cathode material for LiS battery. The initial specific capacity of S/SiO2 /CB (7:2:1) composite is 1184 mAh g −1 and it maintains a 736 mAh g −1 after the 50 th cycle at 0.1 C. The better electrochemical performance is mainly due to the introduction of high content of SiO2 in 7:2:1 composite, in addition to that, the composite contributes to the reduction of the shuttle effect of polysulfides during the cycling process. In this study, S/SiO2 /CB composite exhibits the appreciable capacity without changing its properties. Graphical abstract: Image 1 Highlights: A facile and economical method to prepare S/SiO2 /CB composites via solid state reaction. Carbon wrapped S/SiO2 composites ensure the conductivity of the material. SiO2 enhances the cyclic stability and coulombic efficiency of the electrode. The SSC721 cathode keeps a discharge capacity of 736 mAh g −1 after 50 cycles.